A Contribution to the study of waterbirds in Syrian coast - Alcheikh, Basima (Latakia University Journal -Biological Sciences Series, 2013)
This study aims to define bird species that use artificial lakes in Syrian coast, and evaluate their population size for management and protection of wildlife. Four different sites were chosen in Syrian coast, which considered the most important artificial lakes. Point counts method was used in bird survey in November, December, January, February, March in 2011. 15 waterbird species were recorded belonging to 9 family and 6 order. Wading birds were the main component of waterbird (60% of all species) in Syrian coast. Populations size was 1 to 300 individuals. Diversity of birds and their Populations were greatest in sites which are rich in food ( especially fish). The results showed a difference in composition of bird communities in studied sites.